2002
DOI: 10.1007/s00442-001-0819-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impact of plant structure on host-finding behavior of parasitoids

Abstract: For many parasitoid species, the final step of host location occurs on plants whose structure varies in time and space, altering the capacity of parasitoids to exploit hosts. Plant structure can be defined by its size, heterogeneity and connectivity. We tested the hypothesis that these three components and all possible interactions affect the level of parasitism of Trichogramma evanescens and that parasitism can be predicted if the structure of a plant is measured. We quantified and varied the structure of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 47 publications
2
66
1
3
Order By: Relevance
“…At the scale of individual plants, Andow & Prokrym (1990) and Lukianchuk & Smith (1997) showed that a complex plant architecture not only reduces the probability of an egg parasitoid finding its hosts eggs, but also functionally reduces the parasitoids' searching time depending on the complexity of the plant. Gingras et al (2002) drew the same conclusions from a model of the influence of plant architecture on parasitism rate, which was validated in three natural tritrophic systems. Also at larger spatial scales vegetation structure influences the probability that hosts and patches with hosts are found by parasitoids (Kemp & Simmons, 1978;Price et al, 1980;Finke & Denno, 2002) as well as the abundance of their natural enemies (Langellotto & Denno, 2004).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…At the scale of individual plants, Andow & Prokrym (1990) and Lukianchuk & Smith (1997) showed that a complex plant architecture not only reduces the probability of an egg parasitoid finding its hosts eggs, but also functionally reduces the parasitoids' searching time depending on the complexity of the plant. Gingras et al (2002) drew the same conclusions from a model of the influence of plant architecture on parasitism rate, which was validated in three natural tritrophic systems. Also at larger spatial scales vegetation structure influences the probability that hosts and patches with hosts are found by parasitoids (Kemp & Simmons, 1978;Price et al, 1980;Finke & Denno, 2002) as well as the abundance of their natural enemies (Langellotto & Denno, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…It was expected that a high and complex plant architecture and vegetation structure may both impede host finding by the parasitoid and provide enemy-free space for the egg clutches of the herbivore. Plant architecture was previously defined by the size, heterogeneity and structural complexity of the plant (plant form) (Andow & Prokrym, 1990;Gingras et al, 2002). In this study, this definition was extended to larger spatial scales and plant architecture and vegetation structure were categorized by their height (height of the structure) or structural complexity (number of ramifications, vegetation cover or stalk number; Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…This contradicts the hypothesis that a complex vegetation structure provides a reduced risk of parasitism and that beetles should prefer to oviposit on host plants growing in dense vegetation (Andow & Prokrym, 1990;Gingras et al, 2002;Lukianchuk & Smith, 1997;Romeis et al, 2005).…”
Section: Top-down Effectsmentioning
confidence: 74%
“…"enemy-free space" (Jeffries & Lawton, 1984). It has been reported that a complex plant architecture has a negative effect on the searching efficiency of parasitoids (Andow & Prokrym, 1990;Gingras et al, 2002;Lukianchuk & Smith, 1997;Romeis et al, 2005). Additionally, Obermaier et al (2008) have shown that, in the tansy leaf beetle Galeruca tanaceti L. (Coleoptera: Chrysomelidae), high and dense vegetation close to the oviposition site had a negative effect on egg parasitism.…”
Section: Introductionmentioning
confidence: 99%
“…Sabe-se que o desempenho do parasitoide em campo depende das características fenológicas, bem como da arquitetura da planta. A dinâmica da praga, condições climáticas e estratégias de liberação também são fatores a serem considerados em pesquisas futuras (Gingras et al, 2002 …”
Section: Saccharalisunclassified